Is financial development shaping or shaking economic sophistication in African countries? - Henri Njangang Ndieupa; Simplice Asongu; Sosson Tadadjeu; Yann Nounamo (African Governance and Development Institute (AGDI), 2021)
This paper aims to investigate the effect of financial development on economic complexity using a panel dataset of 24 African countries over the period 1983-2017. The empirical evidence is based on two different approaches. First, we adopt the Hoechle (2007) procedure which produces Driscoll-Kraay standard errors to account for heteroscedasticity and cross-sectional dependence. Second, we implement the system Generalized Method of Moments to account for endogeneity. The results show that financial development increases economic complexity in Africa. Looking at the regional difference, the results show that this effect is less beneficial for SSA countries.
Keywords: G20; G24; E02; P14; O55; 330; Financial development; Economic complexity; Panel data analysis; Africa